Analisis Risiko Kesehatan dan Keselamatan Kerja (K3) dengan Menggunakan Metode Hiradc di Pabrik Tempe Kabupaten Pamekasan - Indah Afifah Cahyani; Fahrurrozi (Reslaj: Religion Education Social Laa Roiba Journal, 2024)
The aim of this research is to create a work environment that is free from work accidents at the tempe factory in Pamekasan district, specifically at the Ibu Syifa tempe factory by applying the HIRADC method. This research uses qualitative methods with the type of field research. Data collection procedures were carried out by interviews, observation and documentation. The results obtained from this research revealed that there were 20 identified hazards, with the results of the risk assessment namely that there were 9 risks categorized as low risk (L) with a value range (1-4), 9 risks categorized as medium risk (M) with a value range (5-9) and 2 more risks which are classified as high risk (H) with a value range of (10-16). Factors that cause work accidents are because workers are not careful in doing so, workers often lose concentration and rush to complete their work. With efforts, one of which is risk analysis using the HIRADC method, factories can reduce work accidents and this can support achieving targets while increasing productivity.